Executive Information System (EIS) to Improve Quality Control and Supervision on Vehicle Maintenance Expenditure - Muhammad Fauzan Azima; Sri Karnila; Hendra Kurniawan (Institut Informatika dan Bisnis Darmajaya, 2018)
Executive Information System (EIS) is a system established to provide information needed by the executive in the decision making process. This information technology is not only used in business activities, but can help an executive in getting an accurate concise picture of the organization. The development of the Executive Information System is used to improve the quality of control and supervision in the Household Section of the Lampung Provincial General Administration Bureau on government official vehicle maintenance expenditures. The research design is classified as Casual Comperative Research. This study aims to develop and implement EIS in the Household Section of the Lampung Provincial Government General Bureau and establish EIS as an implementation of clean government and good government. This system reduces the occurrence of data accumulation and redundancy, so as to prevent the occurrence of indications of corruption, and makes it easier for executives to verify vehicle maintenance data with fairness and rationality with the amount of budget submission. The method used in this study is EIS starting from the stages of planning, implementation, software testing, documentation, deployment and maintenance. So that EIS can control and provide supervision on vehicle maintenance data manipulation that embodies clean government and good government.Keywords: Executive Information System; E-Goverment; Data Manipulation; Monitoring.